Torturous etiquettes film performance and social form - Varndell, Daniel, 1983- (State University of New York Press, 2023)
Explores the ""torture"" of mannered behavior and the prevalence of etiquette as a theme in classical and contemporary Hollywood and European cinema.
Keywords: Etiquette in motion pictures.; Motion pictures -- United States.; Motion pictures -- Europe.; Cinéma -- États-Unis.; PERFORMING ARTS / Film & Video / History & Criticism.; Motion pictures; Europe; United States